Synthesis and electronic properties of a linearly fused anthracene dimer. Issue 31 (30th July 2020) - Onyango, Evans O.; Mannes, Philip Z.; Pletnev, Alexandre; Granger, Devin B.; Ai, Qianxiang; Risko, Chad; Anthony, John E.; Gribble, Gordon W.
Graphical abstract: Highlights: Synthesis of a phenylene-fused dimer of anthracene. A mimic of hexacene that is stable. Electronic properties show through-conjugation but not a fully conjugated acene. Abstract: We describe the synthesis and electronic properties of the novel interrupted hexacene 5, 16-diphenylcyclobuta[1, 2- b :3, 4- b ′]dianthracene (1 ). The synthesis is rooted in a sequential twin Sonogashira coupling of 2, 3-dibromo-9, 10-dihydro-9, 10-epoxyanthracene followed by a Vollhardt 2+2+2 cyclotrimerization to give o- bromoaryl(trimethylsilyl) 8, after selective bromination. A Diels-Alder cycloaddition of the aryne from 8 and 1, 3-diphenylisobenzofuran gave 1 after deoxygenation. Photophysical studies suggest that the fused cyclobutane ring been the two anthracene rings allows through-conjugation, but does not allow 1 to behave as a conjugated acene. Attempts to synthesize the parent analogue, cyclobuta[1, 2- b :3, 4- b ′]dianthracene (2 ) were not successful, but detailed calculations are reported for both 1 and 2 .